Examining the Role of Social Environment in the Relationship between Competence and Entrepreneurial Interest of Vocational Students: A Systematic Literature Review (SLR) - Eko Mety Setyowati; Saiful Arif; Ahmad Andrianto; Yusuf; Andy Prasetyo Wati; Fulgentius Danardana Murwani; Ludi Wishnu Wardana (International Journal of Business and Quality Research, 2025)
This study aims to examine the role of social environment in the relationship between competencies and entrepreneurial interest of Vocational High School (SMK) students. Entrepreneurial competencies, which include practical skills, business knowledge, and creativity, are identified as important factors influencing entrepreneurial interest. However, the social environment-including family, peers, teachers and the local community-has a significant influence in shaping students' attitudes and motivation towards entrepreneurship. This review uses the Systematic Literature Review (SLR) method to identify, evaluate and synthesize findings from previous research relevant to this topic. The results show that a supportive social environment, such as strong family support, entrepreneurial-oriented peers, and education supported by schools, can strengthen the influence of competencies on students' entrepreneurial interest. Conversely, an unsupportive social environment can inhibit entrepreneurial interest despite high competencies. This study concludes that the role of the social environment is crucial in facilitating and strengthening the relationship between competence and entrepreneurial interest, which can contribute to the increase of entrepreneurship among vocational students.